DESIGN-BASED THINKING INTENTIONS AMONG SECONDARY STUDENT-TEACHERS: IMPLICATIONS TO INSTRUCTIONAL DELIVERY - Laarni C. Canare; Ryan R. Pecson, Leandro T. Olubia, Monina S. Romero, Gemma C. Adraneda (CV. ADIBA AISHA AMIRA, 2024)
As future educators, student-teachers must execute the needed deliverables as instructional implementers. However, many still need help once deployed in their respective cooperating schools due to the strenuous tasks they need to do, especially in selecting, designing, developing, and evaluating learning resources. With that in mind, the primordial intention of the study is to examine the design-based thinking intentions among secondary student- teachers deployed in various secondary schools in the divisions of Bataan and Balanga City and implicate the results to instructional delivery. It specifically examines the profile of student-teachers in terms of sex, area of specialization, and location of cooperating school; determines the design-based thinking intentions of student-teachers in terms of understanding (empathizing and defining), exploring (ideating and prototyping), and materializing (testing and implementing); and determines the implications of the findings to effective instructional delivery. Using the descriptive-developmental design of quantitative research, the data are gathered from 172 out of 199 student-teachers under the College of Education (COEd) who are randomly selected. The primary data-gathering tool used in the study is an adopted survey questionnaire. The quantitative data gathered from the study will be analyzed using descriptive statistics (i.e., frequency count, percentage, mean, and standard deviation) and inferential statistics (i.e., T-test and F-test/ANOVA). The results indicate that most respondents are female, majoring in Filipino, English, and Social Studies, and deployed in rural schools. The student- teachers exhibit a high level of design-based thinking intentions across all domains. Also, significant differences are noted in the design-based thinking intentions of student-teachers when grouped according to their profile